O tutorial (Mentoring) na formação do enfermeiro - Rodrigues, Ana Paula Rebelo Aquino (2014)
Nowadays several nursing courses are seeking innovative pedagogical alternatives that can consolidate an education which is more coherent with the desired professional profile for everyday life in health services. One of the alternatives adopted by nursing schools in the country is the methodology known as Tutorial. The aim of this study was to demonstrate the use of the tutorial as learning methodology for nursing education, verify student satisfaction regarding its use and identify the role of tutorial methodology on the construction of student’s critical stance in relation to the reality of health sector. As the tutorial is a student centered methodology where the teacher’s role is to guide them on the development of their professional career and personal life, the study has begun on the hypothesis that the tutorial leads to a meaningful learning, which stimulates the learning process and the student ability to meddle in the reality of the health system in which they are inserted. This was a case study with quantitative and qualitative methodological approach (mixed method). The research’s subjects were students of the second and fifth year of the nursing school at the University of Health Sciences of Alagoas. Data were collected using a structured questionnaire and a problem situation for the student to analyze and narrate their intervention. The answers to the questions were analyzed by Kruskal Wallis non-parametric test with a confidence interval of 95 % (p≤ 0.05) and the problem situation was investigated using content analysis. The results of both analyzes showed that the methodology of the tutorial has the potential to promote the development of a more critical and reflective capacity of the student. However, it is possible to suggest that with the suspension of monitoring due to changes of subjects, or the accumulation of activities throughout the course, students appear to be in process of disengagement, because although they know what must be done, they do not deepen and do not seem to translate into reality.